2004
DOI: 10.1016/j.clpt.2004.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperforin content determines the magnitude of the St John's wort–cyclosporine drug interaction

Abstract: HYF content of SJW extracts significantly affects the extent of the pharmacokinetic interaction between CSA and SJW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 40 publications
6
99
1
5
Order By: Relevance
“…In these studies using other, less sensitive CYP3A substrates (alprazolam, ethinyl estradiol, and cyclosporine A) no interaction was found [12,20]. On the other hand, all 19 studies that used extracts with high hyperforin content showed relevant CYP3A induction [12].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In these studies using other, less sensitive CYP3A substrates (alprazolam, ethinyl estradiol, and cyclosporine A) no interaction was found [12,20]. On the other hand, all 19 studies that used extracts with high hyperforin content showed relevant CYP3A induction [12].…”
Section: Discussionmentioning
confidence: 98%
“…For a mean 11% decrease in exposure to a CYP3A substrate to result in a clinically relevant change in efficacy would require an extremely steep concentration-effect relationship of that CYP3A substrate. In a drug interaction study with cyclosporin A (a narrow therapeutic range CYP3A substrate) and two St. John's wort preparations, cyclosporin A dosage was adjusted only when cyclosporin A trough levels changed by more than 20% [20]. In summary, a minor significant reduction in midazolam AUC (increase in oral midazolam clearance) was found after medication with a St. John's wort powder with low hyperforin content.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many cytochrome P450 (CYP) mediated interactions have been reported between drugs and herbal medicines [1][2][3]. CYP3A4 is the most important human enzyme in the CYP family due to its high relative abundance in the body and its broad substrate specificity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fortes evidências demonstradas em estudos pré-clínicos e ensaios clínicos, sugerem que o extrato de HP interfere no metabolismo citocromodependente de vários fármacos, especialmente por modular o sistema de isoenzimas do citocromo P450 (CYP 450), em especial o CYP3A4, um dos mais importantes desta família (Moore, 2000;Gurley, 2002;Watkins, 2003;Mai, 2004;Gurley, 2005).…”
Section: Interações Medicamentosasunclassified